Manajemen Keselamatan dan Kesehatan Kerja (K3) untuk Mengurangi Risiko Industri dan Dampak Asbes pada Pekerja - Fibi Eko Putra; Tio Ramadan; Saddam Fauzan Akbar; Triana Ambarwati; Muhammad Irfan Jaelani; Arya Maulana Hendri (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Occupational safety and health (K3) is an important factor in ensuring the physical and mental health of workers and creating a safe work environment. This research discusses the implementation of K3 management to minimize work hazards, especially those caused by developments in industrial technology and the use of hazardous materials such as asbestos. As a destructive material, asbestos can cause serious diseases such as lung and pleural cancer if not managed properly. Referring to the K3 management system policy in the Minister of Manpower Decree No. 05 1996, this research emphasizes the important role of company management in integrating K3 into the operating system. It is hoped that the results of this research can serve as a guide for the business world to identify hazards, assess risks, and implement control measures to create a safe and secure work environment.